FIRM REPUTATION AND EXTENT OF WASTE DISCLOSURE - I Gusti Ngurah Manik Maha Putra; Putu Agus Ardiana (Adisam Publisher, 2025)
Waste disclosure represents a crucial aspect of corporate social responsibility, serving to ensure transparency and meet stakeholder expectations. This study aims to analyze the effect of Firm Reputation on the Extent of Waste Disclosure among publicly listed companies in Indonesia. A quantitative approach was employed using Two-Stage Least Squares (2SLS) regression analysis, with secondary data obtained from annual and sustainability reports of companies listed on the Indonesia Stock Exchange. The findings indicate that firms with strong reputations tend to disclose waste-related information more extensively as a strategy to maintain legitimacy in the public eye and to enhance firm value. These results imply that a positive reputation serves as a key driver of environmental transparency.